DETERMINAN PENYALURAN KREDIT MODAL KERJA BANK UMUM UNTUK USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI KOTA TANGERANG - Reza Septian Perdana (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This study aims to identify the factors that influent woking capital loan of commercial banks for Micro, Small, and Medium Enterprises (MSMEs) in Tangerang City. This study uses multiple regression analysis. The result of estimation shows that partially interest rates of working capital loan significantly gives negative influence to woking capital loan distribution ofcommercial banks for MSMEs in Tangerang City. On the contrary, third party funds and exchange rates significantly give positve influence to woking capital loan distribution of commercial banks for MSMEs in Tangerang City. So, it’s needed the effort to increase the capacity of working capital loan through increasing third party funds, set working capital loan interest rates that doesn’t burden MSMEs, keep the stability of exchange rates so that working capital loans distribution of commercial banks for MSMEs in Tangerang City continues to increase.